To Love, Honour and Obey: Wife-battering in Working-Class Montreal, 1869-79 - Harvey, Kathryn (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1990)
This paper aims to reconstruct some of the causes and the context of wife-battering in Montreal between the years 1869-1879. It seeks to determine what the immediate causes were as well as the underlying factors that shaped these conflicts. It also describes how the individuals involved responded, what the role of neighbours was and how this problem was viewed by the society at large. At a broader level, this research seeks to insert one largely ignored aspect of women's lived experience into the historical record while furthering our knowledge of relationships between men and women and working-class family life in general in the mid nineteenth century.